2018
DOI: 10.1016/j.livres.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicles in non-alcoholic and alcoholic fatty liver diseases

Abstract: Fatty liver diseases, non-alcoholic fatty liver disease (NAFLD) and alcoholic liver disease (ALD) are the most common causes of chronic liver disease around the world. NAFLD and ALD can progress towards a more severe form of the disease, including as non-alcoholic steatohepatitis (NASH) and alcoholic steatohepatitis (ASH). In both instances central pathogenic events include hepatocyte death, liver inflammation, pathological angiogenesis, and fibrosis, followed by cirrhosis and cancer. Over the last few years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 49 publications
(59 reference statements)
0
36
0
1
Order By: Relevance
“…A number of studies have demonstrated a role of EVs in both the pathogenesis and progression of NAFLD [14,15]. Triggering of inflammation and fibrosis development are key for progression from isolated steatosis (also referred as NAFL or non-NASH fatty liver) to nonalcoholic steatohepatitis (NASH), which is hallmarked by the presence of hepatocyte ballooning as a reflection of ongoing liver injury and death [36].…”
Section: Evs In Nafldmentioning
confidence: 99%
See 3 more Smart Citations
“…A number of studies have demonstrated a role of EVs in both the pathogenesis and progression of NAFLD [14,15]. Triggering of inflammation and fibrosis development are key for progression from isolated steatosis (also referred as NAFL or non-NASH fatty liver) to nonalcoholic steatohepatitis (NASH), which is hallmarked by the presence of hepatocyte ballooning as a reflection of ongoing liver injury and death [36].…”
Section: Evs In Nafldmentioning
confidence: 99%
“…In this regard, it has been observed that hypoxia determines that fat-laden hepatocytes release EVs able to signal KCs, evoking proinflammatory phenotypes in these cells, a phenomenon that may explain the aggravating effect of obstructive sleep apnea syndrome on NAFLD [71]. Thus, it seems clear that lipotoxic injury of hepatocytes determines EV release, promoting inflammation through activation and recruitment of macrophages [14], with clear implications for the triggering of inflammation in NAFLD/NASH [36]. In addition, hepatocyte-derived EVs may promote HSC activation [47,72] in experimental models of NAFLD/NASH.…”
Section: Evs In Nafldmentioning
confidence: 99%
See 2 more Smart Citations
“…secreted from different cell types send "pro-inflammatory/pro-fibrotic" signals to the liver [15,16]. For instance, Koeck et al observed that exosomes secreted from the visceral adipose tissues of obese patients cause impairment of the TGF-β pathway, which in turn leads to hepatic fibrosis [17].…”
mentioning
confidence: 99%